Identifikasi Pola Morfologi Perkampungan Adat Nagari Koto Hilalang Sumatera Barat Berdasarkan Kearifan Lokal - Siti Aisyah Adelina Putri; Nurini Nurini (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Nagari Koto Hilalang is one of the indigenous villages that located in Gunung Talang district, Solok Regency. This village has been known as one of tourism center in Solok regency referred to the citizen’s activity. The existency of the local wisdom affects the society’s activity due to the pattern of the area’s morphology. The presence of the local wisdom certainly form a morphological pattern and make it unique and different from the other regions. This research questioned the morphology of Nagari Koto Hilalang based on the local wisdom’s morphology. To answer the question of the research, this scientist used the qualitative and quantitative techniques. The analysis result obtained that the morphology pattern of Nagari Koto Hilalang is arranged based on the local wisdom of Minangkabau’s culture, such as taratak, dusun, koto, dan nagari. The rules of society that cause its morphology region belongs to form Organic Pattern where Nagari Koto Hilalang formed naturally/spontaneously because of the growing needs of society that is bound to the custom rule which has been hereditary from ancestors of the minangkabau people. In this study also provided recommendations of referrals for indigenous leaders, government, and community in sustaining indigenous villages (Nagari) morphology of Koto Hilalang.